Platelets are recruited to hepatocellular carcinoma tissues in a CX3CL1‐CX3CR1 dependent manner and induce tumour cell apoptosis - Shuo Miao; Meng Lu; Yue Liu; Dan Shu; Ying Zhu; Wei Song; Yuanyuan Ma; Rong Ma; Bixiang Zhang; Chao Fang; Zhang‐Yin Ming (Molecular Oncology, 2020)
The mechanisms and biological functions of migrating platelets in cancer remain largely unknown. Here, we analyzed platelet infiltration in hepatocellular carcinoma. We detected platelet extravasation in both mouse and human HCC tissues. CX3CL1 directly induced platelet migration, and hypoxia enhanced platelet migration by upregulating CX3CL1 expression. Knocking down CX3CL1 in HCC cells reduced platelet migration in vitro, as well as infiltration of HCC tissue in an orthotopic HCC mouse model. Components of the CX3CR1/Syk/PI3K pathway were essential for CX3CL1‐induced platelet migration. Migrating platelets induced HCC cell apoptosis in vitro, as indicated by a reduced mitochondrial membrane potential and an increased percentage of apoptotic cells. In the orthotopic tumor implantation model, decreased platelet infiltration was associated with accelerated tumor growth. Taken together, our findings indicate that HCC cell‐derived CX3CL1 contributes to tumor infiltration by platelets, which in turn promotes apoptosis of HCC cells.